EV Battery Recycling Adoption: Insights from Dealers and Workshops in Yogyakarta, Indonesia - Ichsanul Fikri Umar Irawana; Annie Purwani (The Indonesian Institute of Science and Technology Research, 2026)
The rapid growth of electric vehicles in Indonesia has intensified battery waste management challenges, while the participation of informal repair businesses in battery recycling services remains limited. Existing studies have largely focused on consumers' recycling behavior, providing little understanding of how informal actors develop the intention to provide recycling services. This study develops a TPB-based behavioral framework by incorporating environmental, social, economic, and technological dimensions as contextual determinants of intention. Survey data from informal repair businesses in Yogyakarta were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that the environmental and technological dimensions significantly influence intention, whereas the social and economic dimensions do not. Intention, in turn, significantly increases willingness to provide battery recycling services. These findings indicate that the underlying behavioral mechanisms of recycling service providers are driven primarily by environmental awareness and technological readiness. This study contributes by elucidating the mechanisms that shape the intentions of recycling service providers, an underexplored stakeholder group in developing countries, and offers practical suggestions for designing interventions that strengthen battery recycling services through environmental education, the provision of appropriate technology, and clear institutional support to encourage participation.